A Galvanic Replacement Route to Prepare Strongly Fluorescent and Highly Stable Gold Nanodots for Cellular Imaging. Issue 3 (8th October 2012) - Wang, Chuanxi; Wang, Yu; Xu, Lin; Shi, Xiaodong; Li, Xiangwei; Xu, Xiaowei; Sun, Hongchen; Yang, Bai; Lin, Quan
Abstract Fluorescent gold nanodots (GNDs) are an important kind of nanoprobes. Herein, the application of galvanic replacement for the preparation of fluorescent GNDs is reported. Using presynthesized and size‐controlled Ag nanodots (Ag NDs) as templates, the as‐prepared GNDs have strong fluorescence (quantum yields ∼10%) with high stability and surface bioactivity. The resultant GNDs show excellent photoluminescence properties with high photo‐, time‐, metal‐, and pH‐stability, which are attributed to the protective surface layer of glutathione (GSH) and the presence of Au(I)–S complexes on the surface of the gold core. GSH, a naturally occurring and readily available tripeptide with carboxyl and amino functional groups, allows good dispersion of the as‐prepared GNDs in aqueous solution and favorable biocompatibility. These advantages, combined with their small size, mean that the as‐prepared GNDs have potential application in biological labeling, especially as a DNA probe for the specific detection of nucleic acids. In this study, the CAL‐27 cells are used as a model to evaluate the fluorescence imaging of GNDs.